The sustainability of wildlife conservation and management in kenya: an examination of trophy hunting in Kenya - Muhuthia, Joshua Kamau (Strathmore University, 2020)
The population of big game animals classified under section 92 of the Wildlife Management and Conservation Act 2013 (in the context of this research, rhinos, lions and elephants) have been on the decline over the past couple of years due to illegal wildlife poaching in spite of the efforts made by the government to combat it. However, in Southern African countries such as South Africa, Zimbabwe, Namibia and Tanzania, they seem to have adopted trophy hunting as a sustainable means of combating illegal wildlife poaching and conservation of these endangered animals. The questions that therefore arise are whether trophy hunting of these endangered species will save them from extinction and whether this method is sustainable for conservation of these species.
Trophy hunting as an activity has its history was done during the medieval times in Europe 1 . This was usually done by rich landowners who had massive tracts of land that they would make sure that they extended to areas with an abundance of wild animals for trophies. During the pre-colonial period, poaching was usually done as a means of African Communities for food and for items like ivory that would be used for trade 3 . This practice was mainly sustainable because of the high population of these wild animals and the low population of indigenous communities. In addition, these communities practiced this hunting with a more conscious attitude towards the well-being of the animals.